Drone Injuries and Safety Recommendations: AE560/AE560, 06/2021 - Gorucu, Serap; Ampatzidis, Yiannis (EDIS, 2021)
This publication presents drone-related injury statistics and safety recommendations to prevent drone-related injuries. Written by Serap Gorucu and Yiannis Ampatzidis, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2021.